Postsecondary Education for First-Generation and Low-Income Students in the Ivy League Navigating Policy and Practice - Landers, Kerry H. (Springer International Publishing, 2018)
This book examines how previously excluded high-achieving, low-income students are faring socially and academically at an Ivy League college in New England. In the past, research conducted on low-income students in elite schools focused mainly on the admissions process. As a result, there is a dearth of research on what happens to low-income students once they are admitted and attend classes. This book chronicles an ethnographic study of twenty low-income men and women in their senior year at Dartmouth College and follows up with them four and twelve years post-graduation. By helping to bring visibility and self-awareness to low-income students and expose class issues and struggles, the author hopes to encourage elite institutions to change their policies and practices to address the needs of these students. .